Revisiting Old Friends: The Production, Distribution and Use of Peterborough Ware in Britain. Issue 1 (February 2015) - Ard, Vincent; Darvill, Timothy
Summary Peterborough Ware is now recognized as the dominant ceramic tradition of the middle Neolithic in southern Britain during the period 3400–2800 BC, part of a wider north European family of Impressed Wares. Drawing on an extensive inventory of 600 recorded assemblages constructed by enriching previous lists with the results of development‐driven research carried out over the last 20 years or so, this paper reviews the production, distribution and use of Peterborough Ware. Support is found for the traditional sub‐division of the Peterborough Ware series into three sub‐styles: Ebbsfleet, Mortlake and Fengate Wares on the basis of the materials used, forms, and the decorative schemes preferred in each. The overall distribution of Peterborough Ware focuses on south‐eastern Britain although there are important assemblages from areas to the west and north, especially those composed of Mortlake Ware. The range of contexts in which Peterborough Ware was deposited is wide, but suggests a backward‐looking attitude in which the users of this style of pottery were trying to connect with their past.